Food restriction and streptozotocin differentially modify sensitivity to the hypothermic effects of direct- and indirect-acting serotonin receptor agonists in rats - Li, Jun-Xu (2009)
Food restriction and experimentally-induced diabetes (streptozotocin) can modify serotonin (5-HT) neurotransmission and sensitivity to drugs acting on 5-HT systems. This study examined the effects of food restriction and streptozotocin on the hypothermic effects of the 5-HT(1A) receptor agonist (+)-8-hydroxy-2-(dipropylamino)tetralin hydrobromide (8-OH-DPAT), the 5-HT(2) receptor agonist (±)-2,5-dimethoxy-4-methylamphetamine hydrochloride (DOM), the 5-HT releaser fenfluramine, and the selective 5-HT reuptake inhibitor (SSRI) fluoxetine. All four drugs significantly decreased body temperature in free feeding rats. Limiting rats to 10 g/day of food for 7 days decreased body weight and sensitivity to 8-OH-DPAT induced hypothermia, without affecting sensitivity to DOM, fenfluramine, or fluoxetine induced hypothermia. Subsequently, 7 days of free feeding restored body weight and sensitivity to 8-OH-DPAT. Sensitivity to all drugs was significantly decreased 7 days after 50 mg/kg streptozotocin; subsequently, 10 days of insulin replacement restored sensitivity to all drugs. These results extend to body temperature the observation that food restriction and experimentally-induced diabetes differentially modify sensitivity to drugs acting on 5-HT systems and they further suggest that the clinical response to therapeutic drugs acting on 5-HT systems might be impacted by nutritional and insulin status.